Gender Differences in Postresuscitative Brain Injury and in the Efficacy of the Immunomodulator Panavir - I. V. Ostrova; M. Sh. Avrushchenko; Yu. V. Zarzhetsky; A. V. Afanasyev; A. V. Volkov (Общая реаниматология)
Objective: to clarify whether gender differences are shown morphofunctional state of the brain of resuscitated animals and in the effects of the immunomodulator panavir. Materials and methods. Adult white rats of both sexes underwent 10-minute cardiac arrest, followed by resuscitation. Panavir was intramuscularly injected in a dose of 0.02 mg/kg at 30 minutes and 24 hours postresuscitation. The neurological status of the resuscitated animals was rated in scores. The density and composition of pyramidal neurons in the CA1 and CA4 hippocampal sectors and those of Purkinje cells in the lateral cerebellum were determined on day 14 after resuscitation. An immune response was assessed by enzyme immunoassay from the plasma levels of tumor necrosis factor-alpha (TNF-a) 24 hours following resuscitation. Results. The resuscitated animals were found to have gender differences in the time of neurological recovery and mortality rates. Panavir treatment was ascertained to result in an increase in the rates of neurological recovery in the resuscitated animals of both sexes. There were gender differences in the postresuscitation changes of the study neuronal populations. Panavir promoted the prevention of neuronal death; however, its efficacy was dissimilar in animals of different sexes. Conclusion. The results of the present study show it necessary to take into account the gender features of the body while developing approaches to pathogeneti-cally sounded prevention and therapy for posthypoxic encephalopathies. Key words: ischemia-reperfusion, neuronal populations, immunomodulators, gender differences.